THE PROBLEM OF HIGHER EDUCATION MANAGEMENT IN THE INTERDISCIPLINARY DISCOURSE OF UKRAINIAN SCIENTISTS (the 90s of the XXth – first quarter of the XXIst centuries) - SAVCHUK, Boris; SNITOVSKA, Olha (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
Purpose of the Research – to carry out a comprehensive synthesized analysis of the reflection of foreign experience in the management and reform of higher education in interdisciplinary research by Ukrainian scholars in the 1990s – the first quarter of the 21st century. The research methodology consists of methods of comparative studies and historiography (periodization, ideographic, historical structural, historical comparative, historical actualization, main array and monographic and selective analysis, analysis of the knowledge system), as well as elements of metaanalysis, content analysis, discourse analysis). The scientific novelty of the research lies in the fact that for the first time in historiography, a substantive analysis of the interdisciplinary Ukrainian discourse on the problem of higher education management in European countries has been carried out and its comparative analysis has been carried out with priority areas of study of the specified problem in the USA, China, etc. Conclusions. The results of the study indicate that foreign experience in higher education management became the subject of active studies by Ukrainian scholars in the 1990s – the first quarter of the 21st century. Their important achievement was a comprehensive understanding of this problem from the standpoint of various fields of knowledge (public administration, history, economics, philosophy of education, comparative pedagogical studies); development of an interdisciplinary methodology for studying the problem; understanding of the complex processes of management of modernization of national higher education systems in historical retrospect and through the prism of Ukraine’s integration into the European Higher Education Area and the challenges of globalization. The features of the dynamics of the studied historiographic process are determined, when in the first period of the 1990s, a number of works appeared that treated the raised problem within the framework of post-Soviet methodological constructs, in the second period, under the influence of the processes of European integration, its study reached a boom in 2006 – 2011/12, and in the third period, there was a gradual fading of scientific interest and the transfer of the accents of its understanding to the context of globalization. The narrow territorial vector of studies was manifested in the focus on studying the history of the development of administrative and reform processes in the countries of Western Europe and the USA, which led to a certain underestimation, with the exception of Poland, of this experience accumulated by the countries of Central and Eastern Europe. We see the prospects for further research in the implementation of a comprehensive comparative analysis of the achievements of Ukrainian and Polish scholars and scientists from other countries on the problems of higher education policy and its reform in the retrospective of the 20th – early 21st centuries. Key words: historiography, higher education management, higher education reform, Western European countries, Central European countries, Eastern European countries.